Peranan Perempuan Pengrajin Noken dalam memenuhi Kebutuhan Sosial Ekonomi Keluarga - Pondayar, Yohan Robert; Lefaan, Avelinus (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2024)
This study aims to analyse the role of women noken crafts in meeting the socio-economic needs of the family, what are the results achieved by women noken crafts in Bhayangkara Village, North Jayapura District, and the obstacles faced in meeting the socio-economic needs of the family. The method used in the research is descriptive qualitative method. The subjects of this research are women noken crafts, Jayapura City Women's Empowerment Office, Bhayangkara Village. Data collection techniques using interview guidelines, observation and documentation techniques. While data analysis uses data editing techniques, data reduction, categorising in units, presenting data, interpreting data, testing data validity and drawing conclusions/verification. The results showed that the role of women noken crafts in Bhayangkara Village, North Jayapura District can be said to be unfavourable, in terms of education, health, and social status. The utilisation of noken bag weaving in Bhayangkara Village, North Jayapura District found inhibiting factors, including: business capital, means of buying and selling, utilisation of models/motifs, and extension of the Jayapura City Women's Empowerment Office. By weaving Noken bags, the women aim to support the daily economy of the Noken crafters' families by realising the local community's socio-economy in terms of income. In other words, the use of Noken bags can affect socioeconomic improvements such as food, clothing, shelter, children's education, health, and ownership of valuables.